Safety and Cost-effectiveness of Outpatient Administration of High-dose Chemotherapy in Children With Ewing Sarcoma. Issue 3 (April 2019) - Elshahoubi, Alya; Alnassan, Anwar; Sultan, Iyad
Abstract : Background: Children with Ewing sarcoma (ES) are subjected to an interval-compressed regimen with cycles of chemotherapy given every 2 weeks, which is nowadays considered to be the standard of care for individuals with such a case. We developed institutional clinical practice guidelines (CPG) applying outpatient administration in regard to this regimen. This study intends to evaluate our institutional experience with this regimen. Methods: We conducted a retrospective review of patients with ES who were treated using interval-compressed protocol of 14 cycles consisting of alternating cyclophosphamide, doxorubicin, vincristine (VDC) and ifosfamide, etoposide (IE) with a maximum dose of doxorubicin of 375 mg/m 2 . Cycles were subsequently followed by G-CSF administration until count recovery was recorded. Patients treated using our guidelines from June 2013 to June 2015 were eligible for these guidelines. Patients younger than 3 years at the time of diagnosis were not eligible for outpatient administration of chemotherapy. Results: In total 12 patients with localized ES or lung-only metastasis were eligible. By the time of analysis, 153 cycles were administered to these patients. Eight cycles for 6 patients were administered on an inpatient basis while the rest (N=145) were administered in the outpatient chemotherapy unit. The median number of cycles per patient were 14 (with a range of 5 to 14). Ninety cycles (59%) were administered on time per CPG. The median interval between these cycles were 16 days (range, 12 to 36 days). The median interval between induction and consolidation cycles were 14 and 17 days, respectively. Neutropenia was reported at the time of each next cycle for 12 cycles. Transient gross hematuria was reported in 1 patient only. In addition, a cost saving of 21% (approximately US 4500) were achieved per patient. Conclusions: Our study showed that the outpatient administration of interval-compressed regimen is safe and associated with acceptable adherence to this regimen.